Do human females use indirect aggression as an intrasexual competition strategy? - Vaillancourt, Tracy (Philos Trans R Soc Lond B Biol Sci, 2013)
Indirect aggression includes behaviours such as criticizing a competitor's appearance, spreading rumours about a person's sexual behaviour and social exclusion. Human females have a particular proclivity for using indirect aggression, which is typically directed at other females, especially attractive and sexually available females, in the context of intrasexual competition for mates. Indirect aggression is an effective intrasexual competition strategy. It is associated with a diminished willingness to compete on the part of victims and with greater dating and sexual behaviour among those who perpetrate the aggression.
Keywords: Body Image; Competitive Behavior; Female; Humans; Male; Sexual Behavior; Women